2018
DOI: 10.1007/s10508-017-1138-7
|View full text |Cite|
|
Sign up to set email alerts
|

Loneliness Mediates the Relationship Between Pain During Intercourse and Depressive Symptoms Among Young Women

Abstract: Previous research suggests that women who experience pain during intercourse also experience higher rates of depressive symptoms. Loneliness might be one factor that contributes to this relationship. We hypothesized that women who experience more severe and interfering pain during intercourse would report higher rates of loneliness and higher rates of depressive symptoms. Further, we hypothesized that loneliness would mediate the relationship between pain during intercourse and depressive symptoms. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 95 publications
2
8
0
3
Order By: Relevance
“…Results of the present study are consistent with some previous findings. For example, the present study replicated the results of the previously conducted pilot study 14 which found strong indirect effects of painful sex on depressive symptoms via loneliness using a cross-sectional study of college women. Various other studies have demonstrated cross-sectional correlations between painful sex and depressive symptoms.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Results of the present study are consistent with some previous findings. For example, the present study replicated the results of the previously conducted pilot study 14 which found strong indirect effects of painful sex on depressive symptoms via loneliness using a cross-sectional study of college women. Various other studies have demonstrated cross-sectional correlations between painful sex and depressive symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…Cross-Sectional Data Sensitivity Analyses. Given that a previous pilot study of cross-sectional data showed relationships between PDI, loneliness, and depressive symptoms, 14 an indirect effects analysis was run using cross-sectional data collected at baseline to determine whether cross-sectional patterns would replicate in the present sample. More severe PDI in the past 4 weeks was associated with greater loneliness (b = 0.584; 99% CI = 0.422 to 0.718), and greater loneliness was associated with greater depressive symptoms (b = 0.328; 99% CI = 0.124 to 0.515).…”
Section: Hypothesis 3: Mediation Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we explored the possibility that loneliness may drive the cluster. Prior small studies have found that loneliness associates with pain, fatigue, and depression in certain specialized populations, including those with complex pain disorders ( Jacobs et al, 2006 ; Jaremka et al, 2014 ; Stout et al, 2018 ; Wolf & Davis, 2014 ). This relationship has yet to be confirmed in a general population of older adults.…”
Section: Introductionmentioning
confidence: 99%